Pemanfatan Media Grafis Dalam Meningkatkan Pemahaman Siswa Mata Pelajaran Fiqih di MTS Darul A’mal - Sawali Fahrizal; Eko Wahyu; Endah Permana Sari; Siti Roudhotul Jannah (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2025)
This study aims to determine the effectiveness of using graphic media in improving students' understanding of the Fiqh subject at MTs Darul Amal. The background of this research is the low level of student comprehension of Fiqh material, which is often abstract and theoretical. The research method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle includes planning, action, observation, and reflection stages. The research subjects were 30 eighth-grade students. Data were collected through observation, comprehension tests, and documentation. The results showed a significant improvement in students' understanding after using graphic media, as indicated by the increase in the average test scores from the first to the second cycle. Furthermore, students showed greater interest and enthusiasm during the learning process. The conclusion of this study is that the use of graphic media is proven to be effective in enhancing students’ understanding of Fiqh at MTs Darul Amal. It is recommended that teachers utilize graphic media more frequently to make learning materials more accessible and engaging. )